9.COMPARING DIALYSIS PATIENTS ACCORDING TO ESTIMATED GLOMERULAR FILTRATION RATE AT DIALYSIS INITIATION AND FIVE YEARS OUTCOME (Iraqi Journal of Medical Sciences, 2019)
Background: It is not clear on which level of estimated glomerular filtration rate to start dialysis until now.Objective: To compare between patient groups according to estimated glomerular filtration rate at dialysis initiation.Methods: Eighty-seven Patients are selected randomly from a list of patients admitted for dialysis (Hemodialysis or Peritoneal dialysis) at Northern General Hospital - Sheffield Kidney Institute from 1st of January to 31st of December 2000. Patients have been categorized into two groups. First group includes 45 patients started dialysis with glomerular filtration rate less than 5 ml/min/1.73m2. Second group includes 42 patients started dialysis with glomerular filtration rate from 5-10 ml/min/1.73m2. Patients have been followed up for five years retrospectively until 31st December 2005.Results: The study showed males are the predominant gender. White Caucasian patients are majority of patients. The mean age is 56 years. About half of patients are middle aged (45-65 years) and are overweight or obese. This study shows no difference between patients who started dialysis early (estimated glomerular filtration rate 5-10 ml/min/1.73m2) versus late (estimated glomerular filtration rate below 5 ml/min/1.73m2) in term of mortality and morbidity throughout five years of follow up.Conclusion: This study showed no justification to decide on time to initiate dialysis based solely on estimated glomerular filtration rate level.Keywords: Chronic kidney disease, estimated glomerular filtration rate, hemodialysis, peritoneal dialysis, end stage renal disease, renal replacement therapyCitation: Al-Joher JAA. Comparing dialysis patients according to estimated glomerular filtration rate at dialysis initiation and five years outcome. Iraqi JMS. 2018; 16(4): 413-423. doi: 10.22578/IJMS.16.4.9
Keywords: Chronic kidney disease; estimated glomerular filtration rate; hemodialysis; peritoneal dialysis; end stage renal disease; renal replacement therapy